Macroeconomic policy: demystifying monetary and fiscal policy - Langdana, Farrokh K. (New York: Springer, 2009)
The book is an applications-oriented text designed for individuals who desire hands-on approach to analyzing the effects of fiscal and monetary policies.
Includes bibliographical references (p. [283]-286) and index.
rua 29/01/14
Loans
Keywords: Macroeconomics; Economic policy; Monetary policy; Fiscal policy